The use of a small enterprise stock market to unlock economic growth in South Africa - Sibiya, Sifiso (My University, 2021)
This study was prompted by concerns about South Africa’s recent economic growth trajectory and the implications that this has on overall living standards. Equally concerning, is the relatively low participation by small enterprises in terms of employment levels, which is a contributing factor the high and rising unemployment rate. In addressing these concerns, this study posits that setting up a stock exchange designed for small enterprises would unlock capital, thus enabling many small enterprises to be growth drivers in the economy. This study has two objectives. The first objective is to explore the features of the proposed small enterprise stock market. This was done by exploring the literature and by presenting a case study of a small enterprise stock market from an emerging markets perspective, called the National Equities Exchange and Quotations (NEEQ) from China. The second objective of this study is to examine whether economic growth can result from a small enterprise stock market. This was done by performing an empirical study of the relationship between small enterprise development and economic growth between 2006 and 2018. The conclusion from this review is that, though weak, there is a causal relationship between small enterprise stock market development and economic growth.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investments to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2021
Keywords: South African stock market; Junior stock exchanges; Granger causality; UCTD; SDG-8: Decent work and economic growth